Implementation Of Patient Rights And Obligations In Health Services In Hospital (Study At Pidie Jaya Regional Hospital) - Sunita Melati Nasution; Sumarno; Bambang Fitrianto (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Healthcare services include all attempts to preserve and enhance a person's health, stop and treat illnesses, and recover their condition. The purpose of this study is to investigate Pidie Jaya Regional Hospital's legal aspects of healthcare services. The study concentrates on the way patients' rights and obligations are carried out and points up the challenges to this process. One used a descriptive method in an empirical study approach. Using both primary and secondary data, data were gathered by observations, interviews, and literary reviews. The results show that Law Number 17 of 2023 on Health rules several areas of healthcare services, including legality, balance, timeliness, good faith, prudence, transparency, autonomy, non-maleficence, beneficence, justice, confidentiality, honesty, and adherence. Patients' rights and obligations are enforced at the Pidie Jaya Regional Hospital by means of processes intended to guarantee that service standards are satisfied and that patients' rights are most respectfully respected. Obstacles such as a lack of knowledge and awareness, problems with facilities and human resources, and administrative and regulatory barriers, however, prevent the full realization of patients' rights and obligations. Notwithstanding these difficulties, Pidie Jaya Regional Hospital has responded to patient complaints by making sure their rights are respected in line with the hospital's dedication and operation as a public health agent. This paper comes to the conclusion that improving service quality depends critically on knowledge and application of pertinent legal components in healthcare services as well as awareness-raising and resource management. It also provides ideas on how satisfying patient rights and enhancing administrative effectiveness in regional hospitals would help to improve healthcare facilities.